JASPER: Phase 2 trial of first‐line niraparib plus pembrolizumab in patients with advanced non–small cell lung cancer. Issue 1 (3rd September 2021) - Ramalingam, Suresh S.; Thara, Eddie; Awad, Mark M.; Dowlati, Afshin; Haque, Basir; Stinchcombe, Thomas E.; Dy, Grace K.; Spigel, David R.; Lu, Sharon; Iyer Singh, Nithya; Tang, Yongqiang; Teslenko, Iryna; et al.
Abstract : Background: Poly(ADP‐ribose) polymerase (PARP) inhibitors may synergize with programmed cell death receptor‐1 (PD‐1) inhibitors to enhance adaptive and innate antitumor immune responses. In the phase 2 JASPER study (NCT04475939), the PARP inhibitor niraparib was evaluated in combination with the PD‐1 inhibitor pembrolizumab in patients with metastatic and/or locally advanced non–small cell lung cancer (NSCLC). Methods: Patients whose tumors had programmed cell death ligand 1 (PD‐L1) tumor proportion scores (TPS) ≥50% (cohort 1) or 1%‐49% (cohort 2) received first‐line niraparib (200 mg once daily) plus pembrolizumab (200 mg every 3 weeks). The primary end point was investigator‐assessed objective response rate (ORR). Secondary end points included duration of response (DoR), progression‐free survival (PFS), overall survival (OS), safety, and pharmacokinetics. Results: Thirty‐eight patients were enrolled in cohorts 1 and 2. In cohort 1, ORR (95% confidence interval [CI]) was 56.3% (9 of 16 patients; 29.9%‐80.2%); 2 of 16 patients had complete responses and 7 of 16 had partial responses (PRs). In cohort 2, ORR was 20.0% (5.7%‐43.7%) with 4 of 20 PRs. In cohorts 1 and 2, the median DoR was 19.7 months (95% CI, 4.2 months to not estimable [NE]) and 9.4 months (95% CI, 4.2 months to NE), the median PFS was 8.4 months (95% CI, 3.9‐22.1 months) and 4.2 months (95% CI, 2.0‐6.2 months), and the median OS was NE (95% CI, 6.0 months to NE) and 7.7 months (95% CI, 4.0‐12.5 months), respectively. Grade ≥3 treatment‐emergent adverse events occurred in 88.2% and 85.7% of patients in cohorts 1 and 2, respectively. Safety was consistent with known profiles of single‐agent niraparib and pembrolizumab. Conclusions: Niraparib plus pembrolizumab showed clinical activity in patients with advanced and/or metastatic NSCLC. Lay Summary: The JASPER clinical trial studied a new combination treatment for advanced or metastatic non–small cell lung cancer (NSCLC). Pembrolizumab, a drug approved for NSCLC, was given with niraparib. Previous research showed that these 2 drugs together might work better than either drug alone. This study found that more than half of patients with high levels of a tumor marker responded to the combination, and one‐fifth of patients with lower levels of the marker responded. The types of side effects from the combination were similar to side effects from both drugs alone. These results support more research on this combination. Abstract : The poly(ADP‐ribose) polymerase inhibitor niraparib, in combination with the programmed cell death receptor 1 inhibitor pembrolizumab, shows clinical activity and a manageable safety profile in patients with advanced or metastatic non–small cell lung cancer (NSCLC) in the phase 2 JASPER study. These results warrant further evaluation of this novel combination in NSCLC.